EFEKTIFITAS EDUKASI DENGAN MEDIA AUDIOVISUAL TERHADAP PENGETAHUAN DAN SIKAP TENTANG GIZI SEIMBANG - Mahmud, Mifta Rahayu; Ambarwati, Ria; Mintarsih, Sri Noor; Prihatin, Setyo (JURNAL RISET GIZI, 2017)
Background  : Knowledge and balanced nutrition attitude in elementary school students is still low, one of them is influenced by the method of nutrition education wich isused lecture method and it does not use media that helps on the acceptance of information and understanding of information provided.Objectives  : To find out the effectiveness of education with audiovisual media toward knowledge and attitude about balanced nutrition at 11 years old students at SDN Bugangan 03 and SDN Rejosari 01.Method  : the research method using Quasi Experiment with desian pretest-posttest gruop one. The number of samples as much as 44 samples, divided into two groups, 22 sample treatment group and the control group sample 22. Statistical analysis using Independent T Test and Mann Whitney. Used to find out the significance of the influence of knowledge and attitudes about nutrition balanced before and after the treatment is done on a confidence level of 95% with the use of statistical software.Result  : Score average of knowledge before treatmet is 67,8and increasebecame 80,4. The score average of attitudebefore treatment is 75.2 increase become 78.9.Conclusion  : Audiovisual media is effective increase knowledge about balanced nutrition. Audiovisual media is not effective in changing attitudes about balanced nutrition.